2016 top trends and issues in Jamaican academic libraries. Issue 1 (9th January 2017) - Harris, Sasekea
Abstract : Purpose: Biennially, the Association of College & Research Libraries (ACRL), a division of the American Library Association, publishes a report on the top trends and issues affecting academic libraries in higher education. Harris (2016) used the trends and issues reported by the ACRL to inform a document and thematic analysis of publications written on Jamaican academic librarianship 2010-2016, to investigate the trends and issues in Jamaican academic librarianship. Harris' (2016) paper however noted that a survey of the chief librarian in each library, regarding their perceptions of the trends and issues would be a useful follow-up to her study, and cited this as a limitation/implication of her paper. The purpose of this paper is to address the above limitation and is therefore the follow-up to Harris' (2016) paper. Design/methodology/approach: The chief librarians in five of the six local university libraries were surveyed to provide insights into the trends and issues in Jamaican academic libraries at the university level. Findings: Acquisitions, budget, staffing, communicating value, digital preservation and curation, mobile environment, collaboration, scholarly communication, information technology, space, higher education, user behaviour and expectations and information literacy are the top trends and issues in Jamaican academic libraries at the university level. Research limitations/implications: This survey seeks to complement rather than contest Harris' (2016) research. Perhaps a useful follow-up to both papers would be biennial updates. Additionally, a survey of the trends and issues in all types of academic libraries throughout the English-speaking Caribbean would be a useful follow-up. Originality/value: This paper is of value, as it is the first survey of trends and issues in Jamaican academic librarianship. It enriches the existing document and thematic analytical research on trends and issues in Jamaican academic libraries by adding an empirical component. It also increases the number of publications, on trends and issues in Jamaican academic librarianship, from one to two, and allows voices from the English-speaking Caribbean (Jamaica) to be incorporated into the literature dedicated to trends and issues in academic libraries.